Answer:
The inverse of f(x) is
![f^(-1) (x) = (2 x+3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/college/rqdiy6b6r4zenp52gairjy1m31nesuszt3.png)
Explanation:
Explanation:-
Given
![f(x) = (4 x-3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/pcdxaq2t3a9mq10uzqfklyoiobw2gwwnt8.png)
Inverse of f(x)
f(x) is a one-one function
let f(x₁) and f(x₂) be two functions are
![f(x_(1) ) = (4 x_(1) -3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/ddd1609nnilglfz01oga56owcwos087z6r.png)
![f(x_(2) ) = (4 x_(2) -3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/ycs0mj8avxzvok4mz94m8as3i5794olz41.png)
⇒
![(4 x_(1) -3)/(2) = (4 x_(2) -3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/1zoodswcvu2y7887py5b271qs1rf0a94ks.png)
⇒ 4 x₁ - 3 = 4 x₂ - 3
⇒ 4 x₁ = 4 x₂
⇒ x₁ = x₂
Given function is one-one function
y = f(x) =
![(4 x-3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/7fvy41npwwfrqhkfpd6wew9j6ihllpeccu.png)
⇒ 2 y = 4 x - 3
⇒ 4 x = 2 y + 3
⇒
![x = (2 y + 3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/college/lovmomw1r6qeojfkgvv9ll2c09uq2jjjpw.png)
⇒ f⁻¹(x)
![= (2 y + 3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/college/s9aii1ssy1i67lcuttwr5j0301hkksgkid.png)
Given function f(x) is onto function
Therefore f(x) is one-one and onto function
![f^(-1) (x) = (2 x+3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/college/rqdiy6b6r4zenp52gairjy1m31nesuszt3.png)